Professional Values and Self-Reported Clinical Competence of Acute Care Nurses in Saudi Arabia: A Cross-Sectional Study - Abdualrahman S. Ashehry; Ergie P. Inocian; Homood A. Alharbi; Naif H. Alanazi; Norisk M. Adalin; Rene P. Carsula; Regie B. Tumala (MDPI AG, 2023)
Background: Professional values are the foundation of nursing practice. Current research evidence on the influence of professional values on clinical competence among acute care nurses in the clinical area is lacking. Purpose: The purpose of this study was to examine the professional values and self-reported clinical competence among acute care nurses. Methods: This quantitative study used a cross-sectional, correlational design. A convenience sample of 403 nurses was recruited to answer the survey utilizing the Nurses Professional Values Scale-3 and the Nurse Competence Scale. The Pearson correlation coefficient was computed to test the relationship between study variables, and a stepwise multiple regression analysis was then performed to investigate the predictors of nurses' professional values and clinical competence. Results: The professional value of "caring" received the highest mean score, followed by "professionalism", while the factor "activism" was rated the lowest. Education was a significant predictor of all three factors of professional values. For clinical competence, "managing situations" was rated as the highest dimension, while "ensuring quality" was rated as the lowest. Moderate positive correlations were revealed between the three factors of professional values and all dimensions of nurses' clinical competence. Area of practice and "activism" were the only significant predictors of the nurses' clinical competence. Conclusions: Nurses perceived all three factors of professional values with high importance in influencing their clinical competence. These findings can contribute to the development of educational interventions to improve and sustain professional values and clinical competence among acute care nurses.